Answer:
x = 1
Step-by-step explanation:
Solving the equations
4x² - 12x + 4 = - 4 ( add 4 to both sides )
4x² - 12x + 8 = 0 ( divide terms by 4 )
x² - 3x + 2 = 0 ← in standard form
(x - 1)(x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
x - 2 = 0 ⇒ x = 2
-------------------------------------
- x² + 4x - 3 = 0 ( multiply through by - 1 )
x² - 4x + 3 = 0 ← in standard form
(x - 1)(x - 3) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
x - 3 = 0 ⇒ x = 3
The solution that is true for both equations is x = 1